Low-temperature sintered and low-loss manganese zinc ferrite material and preparation method thereof

By combining plasma-assisted ball milling and sintering additives, the sintering temperature and power loss of manganese-zeb ferrite materials are reduced, and the problems of high sintering temperature and large power loss in the prior art are solved, thereby achieving the effects of low-temperature sintering and low-loss.

CN119661212APending Publication Date: 2025-03-21SOUTH CHINA UNIV OF TECH
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411795076.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The sintering temperature of existing manganese-zeb ferrite materials is high, resulting in high energy consumption, high carbon emissions, deterioration of magnetic properties, and high power loss.

Method used

By combining plasma-assisted ball milling with specific sintering aid addition, the powder particle size is reduced, liquid phase sintering is introduced, and the system sintering activity is increased, thereby reducing the sintering temperature and power loss of manganese-zeb ferrite material.

Benefits of technology

Low-temperature sintering and low loss of manganese-zeb ferrite material is achieved, reducing the sintering temperature by at least 100°C, reducing energy loss, and improving the performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119661212A_ABST
    Figure CN119661212A_ABST
Patent Text Reader

Abstract

The invention discloses a low-temperature sintered and low-loss manganese zinc ferrite material and a preparation method thereof, and the preparation method comprises the following steps: (1) uniformly mixing Fe2O3, Mn2O3 and ZnO powder, and carrying out mechanical ball milling in water; pre-sintering at the temperature of 850-950 DEG C to obtain a ferrite pre-sintered material; (2) adding a sintering aid containing V2O5 and Al2O3 into the ferrite pre-sintered material to obtain a mixture, and then performing plasma-assisted ball milling to obtain refined powder; preparing a green body sample; and (3) carrying out low-temperature sintering on the green body sample in a nitrogen atmosphere at the sintering temperature of 1050-1250 DEG C for 2-5 hours, and then cooling to obtain the manganese-zinc ferrite material. According to the invention, the densified sintering of the ceramic material is realized at a relatively low temperature (-1200 DEG C) by adding the specific sintering aid and combining with plasma-assisted ball milling, and the power loss value in a relatively wide range is lower than 300kW / m < 3 >.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of manganese-zinc ferrite preparation, and in particular to low-temperature sintered manganese-zinc ferrite and a preparation method thereof. Background Art

[0002] With the rapid development of the electronic information industry, there is an urgent need for the integration, miniaturization and lightweight of equipment. As the soft magnetic material with the largest output and the most extensive application, manganese zinc ferrite is widely used in electronic devices such as switching power supplies, transformers, antennas, etc. due to its high magnetic permeability, high saturation magnetization, high resistivity and low coercivity. At present, the industrial preparation of manganese zinc ferrite generally adopts the ceramic process, and its process flow generally includes the following steps: batching, primary ball milling, pre-sintering, doping, secondary ball milling, granulation and pressing, sintering, etc. However, the current industrial oxide method for preparing manganese zinc ferrite still has the following shortcomings: (1) The ball milling process is all wet ball milling, the obtained powder particle size is large, and the powder sintering activity is poor. (2) Ferrite materials must be prepared by high-temperature sintering. The sintering temperature is generally higher than 1350℃, the sintering time is long, carbon emissions and high energy consumption are generated, discontinuous grains are prone to occur, and the magnetic properties are deteriorated. (3) Ferrite materials have high power loss. Currently, the power consumption of ferrite materials in the range of 25-120°C is generally as high as 300kw / m 3 above.

[0003] At present, the main methods for modifying manganese-zinc ferrite materials based on composition, organization and process adjustment are: (1) Changing the material composition, such as using Cu to replace part of Fe to promote densification and reduce porosity. (2) Adding sintering aids, such as some low-melting-point oxides (V2O5, Bi2O3, etc.) or glass flux, to assist the sintering process in liquid form during the sintering process. (3) Refining the powder, reducing the powder particle size by extending the ball milling time, increasing the ball milling speed or changing the process control agent. (4) Improving the sintering process, introducing other forms of energy to replace part of the thermal energy during the pressureless sintering process, thereby reducing the sintering temperature.

[0004] In order to reduce the particle size of powder and improve the sintering activity of powder, the invention patent with publication number CN 112723872 B discloses a manganese-zinc ferrite pre-sintered material and its preparation process. It can convert inert gas into plasma by dielectric barrier discharge. Under the action of the electric field, the charged particles moving at high speed will directly act on the powder particles, and work together with the mechanical energy generated during the ball milling process to accelerate the powder refinement, improve the refinement efficiency of ball milling, and improve the sintering activity of powder. However, although the use of plasma-assisted ball milling can refine the powder and improve the sintering activity of the powder, it still cannot make up for the sintering activity reduced by the lower sintering temperature. Summary of the invention

[0005] The object of the present invention is to provide a manganese-zinc ferrite material with low sintering temperature and low loss and a preparation method thereof. By combining plasma-assisted ball milling with the addition of a specific sintering aid, the powder particle size is reduced, liquid phase sintering is introduced, and the sintering activity of the system is increased, thereby reducing the sintering temperature of the manganese-zinc ferrite material and reducing the power loss of the ferrite material, thereby reducing carbon emissions and improving the performance of the manganese-zinc ferrite material.

[0006] The technical solution adopted by the present invention is as follows:

[0007] A method for preparing a low-temperature sintered and low-loss manganese-zinc ferrite material comprises the following steps:

[0008] (1) Fe2O3, Mn2O3 and ZnO powders are uniformly mixed and mechanically ball-milled in water; the obtained material is pre-sintered at 850-950°C for 2-4 hours and cooled in the furnace to obtain a ferrite pre-sintered material;

[0009] (2) adding the following additives to the ferrite pre-sintered material: by mass percentage, CaO: 0.02-0.20%, SiO2: 0.01-0.08%, TiO2: 0.08-0.20%, Co2O3: 0.05-0.18%, V2O5: 0.01-0.40%, Al2O3: 0.01-0.40%, and preliminarily mixing to obtain a mixture, and plasma-assisted ball milling to obtain a refined powder; the refined powder is granulated and pressed to prepare a standard green sample;

[0010] (3) The green sample obtained in step (2) is subjected to low-temperature sintering in a nitrogen atmosphere at a sintering temperature of 1050-1250° C. for a sintering time of 2-5 h, and then cooled to obtain a manganese-zinc ferrite material.

[0011] Preferably, in step (1), the raw material ratio, measured by mole percentage, is Fe2O3: 50-55%, ZnO: 10-15%, and Mn2O3: 30-40%.

[0012] Preferably, the ball milling medium of the plasma-assisted ball milling is a tungsten steel alloy grinding ball.

[0013] Preferably, the ball-to-material ratio of the plasma-assisted ball milling is (40-50):1, and the ball milling time is 15-45 min.

[0014] Preferably, the vibration frequency of the plasma-assisted ball milling in step (2) is 300 to 1200 Hz.

[0015] Preferably, after the plasma-assisted ball milling is run once, it is stopped for 15 to 25 minutes before the next plasma-assisted ball milling is continued, and the number of plasma-assisted ball milling is 6 to 10 times.

[0016] Preferably, the plasma discharge current is 180-250 mA, the discharge voltage is 4.1-4.8 kV, and the discharge frequency is 9-10 kHz.

[0017] Preferably, the temperature rising procedure of the low temperature sintering is: first sinter at 200-400°C for 1±0.5h, and then sinter at 1200±50°C for 3±0.5h.

[0018] Preferably, the mechanical ball milling in step (1) adopts a planetary ball mill, the ball milling medium is stainless steel grinding balls, the ball-to-material ratio is 4±1:1, the ball milling time is 4-6 hours, the ball milling speed is 250±100r / min, and the material liquid after mechanical ball milling is dried at a temperature of 90-120°C for 6-12 hours; the heating program is: heating at a rate of 2.5-4.5°C / min to 300±50°C, keeping warm for 1±0.5h, and then heating to 1200°C at a rate of 3-5°C / min, and keeping warm for 3±0.5h.

[0019] Preferably, the step of plasma-assisted ball milling in step (2) is to place the mixed material in a ball mill and wet it with anhydrous ethanol; after evacuating the ball mill, an inert gas is introduced into the ball mill at a pressure of 5×10 -3 ~5×10 -2 MPa, and then ball milling is performed; the nitrogen flow rate in step (3) is 0.01-0.3 L / min.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] (1) The present invention introduces a VA sintering aid (V2O5:Al2O3=1:1) into the system, aiming to introduce liquid phase sintering into the solid phase sintering mechanism and promote the sintering process. The melting point of vanadium oxide is about 690°C. It exists in the liquid phase during the sintering process, wets and dissolves the solid phase particles, and is conducive to homogenizing the microstructure and reducing the porosity. However, excessive addition of vanadium oxide will cause abnormal growth of grains and deteriorate the magnetic properties. The melting point of aluminum oxide is about 2072°C. It is distributed at the grain boundary and inhibits the rapid growth of grains during the sintering process, improves the uniformity of the organization, and reduces power loss. However, excessive aluminum oxide will cause excessive grain refinement and deteriorate the magnetic properties. Therefore, in order to reduce the sintering temperature while maintaining the soft magnetic properties, the two are added to the ferrite in a certain proportion to improve the degree of homogenization of the sample organization.

[0022] (2) The present invention introduces cold field plasma during the ball milling process, and the temperature of its charged particles is relatively high. During the charge and discharge process, the powder surface repeatedly rises and falls in temperature, introducing thermal stress. At the same time, the charged particles bombard the powder surface under the acceleration of the electric field, generating a large number of defects. Assisted by mechanical ball milling, it is extremely beneficial to powder crushing and refinement, and shortening the powder particle size range. The reduction of powder particle size and the generation of a large number of surface defects can increase the specific surface area of ​​the powder, thereby increasing the surface energy of the powder, so that the powder needs to obtain energy from the outside during the subsequent sintering process. In addition, the narrowing of the particle size range can make the solid phase reaction inside the green body uniform during the subsequent sintering process, reducing the possibility of secondary grain growth. In general, plasma-assisted ball milling can achieve powder refinement, increase powder surface energy, and increase powder sintering activity, thereby improving the uniformity and density of the sample during sintering, and reducing the possibility of cracking and deformation of the final product. The overall process is flexible and highly adjustable.

[0023] (3) The present invention realizes the densification sintering of ferrite materials at a relatively low temperature by means of plasma-assisted ball milling and the addition of specific sintering aids. The power loss value of the obtained manganese-zinc ferrite material is less than 300kW / m in the temperature range of f<150kHz, Bs<200mT and 25℃-120℃. 3 Compared with the traditional sintering temperature of more than 1350℃, the sintering temperature can be reduced by at least 100℃, which further reduces the energy loss in the production and preparation process and achieves the effect of energy saving and emission reduction. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1a , Figure 1b They are the particle size distribution diagrams of the manganese zinc ferrite ball-milled powder in comparative example 1 (vibration frequency is 300 Hz) and example 1 (plasma-assisted ball milling).

[0025] Figure 2a , Figure 2b , Figure 2c , Figure 2d They are the secondary electron images of the manganese-zinc ferrite materials in Comparative Example 1 (no VA sintering aid added + ball milling with a vibration frequency of 300 Hz), Comparative Example 2 (VA sintering aid added + ball milling with a vibration frequency of 300 Hz), Comparative Example 3 (no VA sintering aid added + plasma-assisted ball milling) and Example 1 (VA sintering aid added + plasma-assisted ball milling).

[0026] Figure 3These are the XRD spectra of the manganese-zinc ferrite materials in Comparative Example 1 (no VA sintering aid added + ball milling with a vibration frequency of 300 Hz), Comparative Example 2 (VA sintering aid added + ball milling with a vibration frequency of 300 Hz), Comparative Example 3 (no VA sintering aid added + plasma-assisted ball milling) and Example 1 (VA sintering aid added + plasma-assisted ball milling).

[0027] Figure 4 The density and average grain size diagram of the manganese-zinc ferrite materials in Comparative Example 1 (no VA sintering aid added + ball milling with a vibration frequency of 300 Hz), Comparative Example 2 (VA sintering aid added + ball milling with a vibration frequency of 300 Hz), Comparative Example 3 (no VA sintering aid added + plasma-assisted ball milling) and Example 1 (VA sintering aid added + plasma-assisted ball milling).

[0028] Figure 5 It is a bar graph of the saturation magnetic induction intensity of the manganese-zinc ferrite materials in Comparative Example 1 (no VA sintering aid added + ball milling with a vibration frequency of 300 Hz), Comparative Example 2 (VA sintering aid added + ball milling with a vibration frequency of 300 Hz), Comparative Example 3 (no VA sintering aid added + plasma-assisted ball milling) and Example 1 (VA sintering aid added + plasma-assisted ball milling).

[0029] Figure 6 It is a bar graph of the initial magnetic permeability and a curve graph of the cutoff frequency change of the manganese-zinc ferrite materials in Comparative Example 1 (no VA sintering aid added + ball milling with a vibration frequency of 300 Hz), Comparative Example 2 (VA sintering aid added + ball milling with a vibration frequency of 300 Hz), Comparative Example 3 (no VA sintering aid added + plasma-assisted ball milling) and Example 1 (VA sintering aid added + plasma-assisted ball milling).

[0030] Figure 7 The frequency characteristic curves of power loss of manganese-zinc ferrite materials in comparative example 1 (no VA sintering aid added + ball milling with a vibration frequency of 300 Hz), comparative example 2 (VA sintering aid added + ball milling with a vibration frequency of 300 Hz), comparative example 3 (no VA sintering aid added + plasma-assisted ball milling) and embodiment 1 (VA sintering aid added + plasma-assisted ball milling) are shown.

[0031] Figure 8 The temperature characteristic curves of power loss of manganese-zinc ferrite materials in comparative example 1 (no VA sintering aid added + ball milling with a vibration frequency of 300 Hz), comparative example 2 (VA sintering aid added + ball milling with a vibration frequency of 300 Hz), comparative example 3 (no VA sintering aid added + plasma-assisted ball milling) and embodiment 1 (VA sintering aid added + plasma-assisted ball milling) are shown. DETAILED DESCRIPTION

[0032] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. The present invention is further described in conjunction with the embodiments:

[0033] Comparative Example 1

[0034] (1) In terms of molar mass percentage, 53.5% of iron oxide, 34.5% of manganese oxide and 12% of zinc oxide were placed in a ball mill, and deionized water four times the mass of the powder was added as a ball milling medium. Stainless steel grinding balls were added to the ball mill, and the ball-to-material ratio was 4:1. The ball milling was performed for 4 hours, and the obtained slurry was dried at 110° C. for 6 hours;

[0035] (2) pre-sintering the material obtained in step (1) at 900° C. for 2 h, and cooling the furnace to obtain a ferrite pre-sintered material;

[0036] (3) adding the following additives by weight to the ferrite pre-sintered material obtained in step (2): CaO: 0.10%, SiO2: 0.04%, TiO2: 0.20%, Co2O3: 0.10%, V2O5: 0.03%, and performing preliminary mixing to obtain a mixed material;

[0037] (4) placing the mixed material obtained above into a ball mill, adding alloy grinding balls as ball milling media into the ball mill, with a ball-to-material ratio of 50:1;

[0038] (5) adjusting the ball mill vibration frequency to 300 Hz, and setting the ball milling time to stop for 20 minutes after each 30 minutes of ball milling, with a cycle of 8 times, to obtain a refined mixed powder;

[0039] (6) The refined powder obtained in step (5) is mixed with an 8% by mass % PVA aqueous solution, and the mixed powder is sieved through 60 and 180 mesh sieves, and sifted three times continuously to complete granulation, and obtain a refined manganese-zinc ferrite powder with good fluidity; the granulated powder is weighed and poured into a mold to be pressed into a ring-shaped green body, and the pressing pressure is controlled to 300 MPa. The size of the ring green body is 20 mm in outer diameter, 12 mm in inner diameter, and 5 mm in height.

[0040] (7) The green body is placed in a nitrogen atmosphere furnace for heat treatment. During the heat treatment, the temperature is increased to 300°C at a rate of 3°C / min, kept at this temperature for 1 h, then increased to 900°C at a rate of 5°C / min, then increased to 1200°C at a rate of 3°C / min, kept at this temperature for 3 h, then decreased to 200°C at a rate of 5°C / min, and finally naturally cooled to room temperature.

[0041] Figure 1a This is the particle size distribution diagram of the powder obtained in step (5) of Comparative Example 1. After ball milling at a vibration frequency of 300 Hz, the powder particle size range is determined to be 0.30 to 11.15 μm.

[0042] Figure 2a This is a secondary electron image of the manganese-zinc ferrite material obtained by ball milling at a vibration frequency of 300 Hz without adding VA sintering aid in Comparative Example 1. During the sintering process, the sintering temperature is low, the powder size is large, the grain size of the structure is fine, and the degree of densification is low.

[0043] The XRD pattern of the manganese-zinc ferrite material obtained by ball milling at a vibration frequency of 300 Hz in Comparative Example 1 without adding VA sintering aid is shown in Figure 3 .

[0044] In Comparative Example 1, no VA sintering aid was added and the density and average grain size of the manganese-zinc ferrite material obtained by ball milling at a vibration frequency of 300 Hz are shown in Figure 4 The density of the manganese-zinc ferrite material is determined to be 4.6506 g / cm 3 , the average grain size is 3.97μm.

[0045] In comparative example 1, no VA sintering aid was added and the saturation magnetic induction intensity of the manganese-zinc ferrite material obtained by ball milling at a vibration frequency of 300 Hz is shown in FIG. Figure 5 The saturation magnetic induction intensity of the manganese-zinc ferrite material was determined to be 492.18 mT.

[0046] In Comparative Example 1, no VA sintering aid was added and the initial magnetic permeability and cutoff frequency of the manganese-zinc ferrite material obtained by ball milling at a vibration frequency of 300 Hz are shown in Figure 6 The cut-off frequency of the manganese-zinc ferrite material is determined to be 5.34MHz. At a frequency of 10kHz, the starting permeability value of the manganese-zinc ferrite material is 674.68.

[0047] The frequency characteristic curve and temperature characteristic curve of power loss of manganese-zinc ferrite material obtained by ball milling at a vibration frequency of 300 Hz in comparative example 1 without adding VA sintering aid are shown in Figure 7 and Figure 8 .

[0048] Comparative Example 2

[0049] (1) In terms of molar mass percentage, 53.5% of iron oxide, 34.5% of manganese oxide and 12% of zinc oxide were placed in a ball mill, and deionized water four times the mass of the powder was added as a ball milling medium. Stainless steel grinding balls were added to the ball mill, and the ball-to-material ratio was 4:1. The ball milling was performed for 4 hours, and the obtained slurry was dried at 110° C. for 6 hours;

[0050] (2) pre-sintering the material obtained in step (1) at 900° C. for 2 h, and cooling the furnace to obtain a ferrite pre-sintered material;

[0051] (3) adding the following additives by weight to the ferrite pre-sintered material obtained in step (2): CaO: 0.10%, SiO2: 0.04%, TiO2: 0.20%, Co2O3: 0.10%, V2O5: 0.10%, Al2O3: 0.10%, and performing preliminary mixing to obtain a mixed material;

[0052] (4) placing the mixed material obtained above into a ball mill, adding alloy grinding balls as ball milling media into the ball mill, with a ball-to-material ratio of 50:1;

[0053] (5) adjusting the ball mill vibration frequency to 300 Hz, and setting the ball milling time to stop for 20 minutes after each 30 minutes of ball milling, with a cycle of 8 times, to obtain a refined mixed powder;

[0054] (6) The refined powder obtained in step (5) is mixed with an 8% by mass % PVA aqueous solution, and the mixed powder is sieved through 60 and 180 mesh sieves, and sifted three times continuously to complete granulation, and obtain a refined manganese-zinc ferrite powder with good fluidity; the granulated powder is weighed and poured into a mold to be pressed into a ring-shaped green body, and the pressing pressure is controlled to 300 MPa. The size of the ring green body is 20 mm in outer diameter, 12 mm in inner diameter, and 5 mm in height.

[0055] (7) The green body is placed in a nitrogen atmosphere furnace for heat treatment. During the heat treatment, the temperature is increased to 300°C at a rate of 3°C / min, kept at this temperature for 1 h, then increased to 900°C at a rate of 5°C / min, then increased to 1200°C at a rate of 3°C / min, kept at this temperature for 3 h, then decreased to 200°C at a rate of 5°C / min, and finally naturally cooled to room temperature.

[0056] Figure 2b This is a secondary electron image of the manganese-zinc ferrite material obtained by adding VA sintering aid and ball milling at a vibration frequency of 300 Hz in Comparative Example 2. After adding a certain amount of VA sintering aid, liquid phase sintering is introduced into solid phase sintering. During the sintering process, the particles are wetted and dissolved, the grains grow uniformly, the microstructure becomes dense, and the number of pores is significantly reduced.

[0057] The XRD pattern of the manganese-zinc ferrite material obtained by adding VA sintering aid and ball milling at a vibration frequency of 300 Hz in Comparative Example 2 is shown in FIG. Figure 3 .

[0058] The density and average grain size of the manganese-zinc ferrite material obtained by adding VA sintering aid and ball milling at a vibration frequency of 300 Hz in Comparative Example 2 are shown in Table 2. Figure 4 The density of the manganese-zinc ferrite material is determined to be 4.7788 g / cm3 , the average grain size is 4.62μm.

[0059] The saturation magnetic induction intensity diagram of the manganese-zinc ferrite material obtained by adding VA sintering aid and ball milling at a vibration frequency of 300 Hz in Comparative Example 2 is shown in FIG. Figure 5 The saturation magnetic induction intensity of the manganese-zinc ferrite material was determined to be 507.68 mT.

[0060] The initial magnetic permeability and cutoff frequency of the manganese-zinc ferrite material obtained by adding VA sintering aid and ball milling at a vibration frequency of 300 Hz are shown in Figure 6 The cut-off frequency of the manganese-zinc ferrite material is determined to be 4.65MHz. At a frequency of 10kHz, the starting permeability value of the manganese-zinc ferrite material is 1045.92.

[0061] The frequency characteristic curve and temperature characteristic curve of the power loss of the manganese-zinc ferrite material obtained by adding VA sintering aid and ball milling at a vibration frequency of 300 Hz in Comparative Example 2 are shown in Figure 7 and Figure 8 .

[0062] Comparative Example 3

[0063] (1) In terms of molar mass percentage, 53.5% of iron oxide, 34.5% of manganese oxide and 12% of zinc oxide were placed in a ball mill, and deionized water four times the mass of the powder was added as a ball milling medium. Stainless steel grinding balls were added to the ball mill, and the ball-to-material ratio was 4:1. The ball milling was performed for 4 hours, and the obtained slurry was dried at 110° C. for 6 hours;

[0064] (2) pre-sintering the material obtained in step (1) at 900° C. for 2 h, and cooling the furnace to obtain a ferrite pre-sintered material;

[0065] (3) adding the following additives by weight to the ferrite pre-sintered material obtained in step (2): CaO: 0.10%, SiO2: 0.04%, TiO2: 0.20%, Co2O3: 0.10%, V2O5: 0.03%, and performing preliminary mixing to obtain a mixed material;

[0066] (4) placing the mixed material obtained above into a ball mill, adding alloy grinding balls as ball milling media into the ball mill, with a ball-to-material ratio of 50:1;

[0067] (5) Pump the air pressure in the ball mill to 5×10 -3MPa or less, turn on the plasma-assisted high-energy ball milling device for plasma-assisted ball milling, adjust the ball milling vibration frequency to 1200 Hz, modulate the working current to 190 mA, modulate the excitation voltage to 4.4 kV, modulate the excitation frequency to 8.7 kHz, and set the ball milling time to stop for 20 minutes after each ball milling for 30 minutes, with a cycle of 8 times, to obtain a refined mixed powder;

[0068] (6) The refined powder obtained in step (5) is mixed with an 8% by mass % PVA aqueous solution, and the mixed powder is sieved through 60 and 180 mesh sieves, and sifted three times continuously to complete granulation, and obtain a refined manganese-zinc ferrite powder with good fluidity; the granulated powder is weighed and poured into a mold to be pressed into a ring-shaped green body, and the pressing pressure is controlled to 300 MPa. The size of the ring green body is 20 mm in outer diameter, 12 mm in inner diameter, and 5 mm in height.

[0069] (7) The green body is placed in a nitrogen atmosphere furnace for heat treatment. During the heat treatment, the temperature is increased to 300°C at a rate of 3°C / min, kept at this temperature for 1 h, then increased to 900°C at a rate of 5°C / min, then increased to 1200°C at a rate of 3°C / min, kept at this temperature for 3 h, then decreased to 200°C at a rate of 5°C / min, and finally naturally cooled to room temperature.

[0070] Figure 2c This is a secondary electron image of the manganese-zinc ferrite material obtained by plasma-assisted ball milling without adding VA sintering aid in Comparative Example 3. After ball milling and sintering, the particles sintered to form a dense block. The powder particle size obtained by plasma-assisted ball milling is finer. At the same time, due to the characteristics of the plasma itself, the sintering activity of the powder is improved during the ball milling process. Therefore, an appropriate grain size can be obtained at a relatively low sintering temperature (1200°C), and the degree of organizational densification is high.

[0071] The XRD pattern of the manganese-zinc ferrite material obtained by plasma-assisted ball milling without adding VA sintering aid in Comparative Example 3 is shown in Figure 3 .

[0072] The XRD pattern of the manganese-zinc ferrite material obtained by plasma-assisted ball milling without adding VA sintering aid in Comparative Example 3 is shown in Figure 3 .

[0073] In Comparative Example 3, no VA sintering aid was added and the density and average grain size of the manganese-zinc ferrite material obtained by plasma-assisted ball milling were shown in Figure 4 The density of the manganese-zinc ferrite material is determined to be 4.7755 g / cm 3 , the average grain size is 4.58μm.

[0074] The saturation magnetic induction intensity diagram of the manganese-zinc ferrite material obtained by plasma-assisted ball milling without adding VA sintering aid in Comparative Example 3 is shown in Figure 5 The saturation magnetic induction intensity of the manganese-zinc ferrite material was determined to be 505.95 mT.

[0075] The initial permeability and cutoff frequency of the manganese-zinc ferrite material obtained by plasma-assisted ball milling without adding VA sintering aid in Comparative Example 3 are shown in Figure 6 The cut-off frequency of the manganese-zinc ferrite material is determined to be 5.10MHz. At a frequency of 10kHz, the starting permeability value of the manganese-zinc ferrite material is 946.19.

[0076] The frequency characteristic curve and temperature characteristic curve of power loss of the manganese-zinc ferrite material obtained by plasma-assisted ball milling without adding VA sintering aid in comparative example 3 are shown in Figure 7 and Figure 8 .

[0077] Example 1

[0078] (1) In terms of molar mass percentage, 53.5% of iron oxide, 34.5% of manganese oxide and 12% of zinc oxide were placed in a ball mill, and deionized water four times the mass of the powder was added as a ball milling medium. Stainless steel grinding balls were added to the ball mill, and the ball-to-material ratio was 4:1. The ball milling was performed for 4 hours, and the obtained slurry was dried at 110° C. for 6 hours;

[0079] (2) pre-sintering the material obtained in step (1) at 900° C. for 2 h, and cooling the furnace to obtain a ferrite pre-sintered material;

[0080] (3) adding the following additives by weight to the ferrite pre-sintered material obtained in step (2): CaO: 0.10%, SiO2: 0.04%, TiO2: 0.20%, Co2O3: 0.10%, V2O5: 0.10%, Al2O3: 0.10%, and performing preliminary mixing to obtain a mixed material;

[0081] (4) placing the mixed material obtained above into a ball mill, adding alloy grinding balls as ball milling media into the ball mill, with a ball-to-material ratio of 50:1;

[0082] (5) Pump the air pressure in the ball mill to 5×10 -3 MPa or less, turn on the plasma-assisted high-energy ball milling device for plasma-assisted ball milling, adjust the ball milling vibration frequency to 1200 Hz, modulate the working current to 190 mA, modulate the excitation voltage to 4.4 kV, modulate the excitation frequency to 8.7 kHz, and set the ball milling time to stop for 20 minutes after each ball milling for 30 minutes, with a cycle of 8 times, to obtain a refined mixed powder;

[0083] (6) The refined powder obtained in step (5) is mixed with a PVA aqueous solution having a mass fraction of 8%, and the mixed powder is sieved through a 60-mesh sieve and a 180-mesh sieve for three consecutive times to obtain a refined manganese-zinc ferrite powder with good fluidity; the granulated powder is weighed and poured into a mold to be pressed into a ring-shaped green body, the pressing pressure is controlled to be 300 MPa, and the size of the ring green body is 20 mm in outer diameter, 12 mm in inner diameter, and 5 mm in height.

[0084] (7) The green body is placed in a nitrogen atmosphere furnace for heat treatment. During the heat treatment, the temperature is increased to 300°C at a rate of 3°C / min, kept at this temperature for 1 h, then increased to 900°C at a rate of 5°C / min, then increased to 1200°C at a rate of 3°C / min, kept at this temperature for 3 h, then decreased to 200°C at a rate of 5°C / min, and finally naturally cooled to room temperature.

[0085] Figure 1b This is the particle size distribution diagram of the powder obtained in step (5) of Example 1. After plasma-assisted ball milling, the powder particle size range is determined to be 0.27 to 5.18 μm.

[0086] Figure 2d The secondary electron image of the manganese-zinc ferrite material obtained by adding VA sintering aid and plasma-assisted ball milling in Example 1. A quantitative VA sintering aid was added, and the manganese-zinc ferrite material obtained after plasma-assisted ball milling formed a dense block after sintering. The powder obtained by plasma-assisted ball milling has a finer particle size and high surface energy, and the VA sintering aid exists in the form of liquid phase during the sintering process. The high sintering activity powder is wetted and dissolved by the liquid phase. At a relatively low sintering temperature (1200°C), the grains grow uniformly, the microstructure is homogenized and the degree of densification is high, the grain boundaries are clear and the number of pores is small.

[0087] The XRD pattern of the manganese-zinc ferrite material obtained by adding VA sintering aid and plasma-assisted ball milling in Example 1 is shown in Figure 3 .

[0088] The density and average grain size of the manganese-zinc ferrite material obtained by adding VA sintering aid and plasma-assisted ball milling in Example 1 are shown in Figure 4 The density of the manganese-zinc ferrite material was determined to be 4.8211 g / cm 3 The average grain size is 5.10 μm. The density of the manganese-zinc ferrite material obtained in Comparative Example 1 is 4.6506 g / cm 3 ) and the average grain size (3.97 μm), the density of the manganese-zinc ferrite material prepared in this embodiment increased by 3.67%, and the average grain size increased by 28.46%. The density of the manganese-zinc ferrite material obtained in Comparative Example 2 (4.7788 g / cm 3) and the average grain size (4.62 μm), the density of the manganese-zinc ferrite material prepared in this embodiment increased by 0.89%, and the average grain size increased by 10.39%. The density of the manganese-zinc ferrite material obtained in Comparative Example 3 (4.7755 g / cm 3 ) and the average grain size (4.58 μm), the density of the manganese-zinc ferrite material prepared in this embodiment increased by 0.95%, and the average grain size increased by 11.35%. By comparing the variance values ​​of the average grain sizes of each group, the manganese-zinc ferrite material prepared in this embodiment has a smaller variance value, a high degree of homogenization of the grain size, and a more uniform structure.

[0089] The saturation magnetic induction intensity diagram of the manganese-zinc ferrite material obtained by adding VA sintering aid and plasma-assisted ball milling in Example 1 is shown in FIG. Figure 5 . The saturation magnetic induction intensity of the manganese-zinc ferrite material was determined to be 511.83 mT. Compared with the saturation magnetic induction intensity (492.18 mT) of the manganese-zinc ferrite material obtained in Comparative Example 1, the saturation magnetic induction intensity of the manganese-zinc ferrite material prepared in this embodiment increased by 3.99%. Compared with the saturation magnetic induction intensity (507.68 mT) of the manganese-zinc ferrite material obtained in Comparative Example 2, the saturation magnetic induction intensity of the manganese-zinc ferrite material prepared in this embodiment increased by 0.82%. Compared with the saturation magnetic induction intensity (505.95 mT) of the manganese-zinc ferrite material obtained in Comparative Example 3, the saturation magnetic induction intensity of the manganese-zinc ferrite material prepared in this embodiment increased by 1.16%.

[0090] The initial permeability and cutoff frequency of the manganese-zinc ferrite material obtained by adding VA sintering aid and plasma-assisted ball milling in Example 1 are shown in Figure 6 . The cutoff frequency of the manganese-zinc ferrite material is determined to be 4.44 MHz. At a frequency of 10 kHz, the initial magnetic permeability value of the manganese-zinc ferrite material is 1232.38. Compared with the initial magnetic permeability value (674.68) of the manganese-zinc ferrite material obtained in Comparative Example 1, the initial magnetic permeability value of the manganese-zinc ferrite material prepared in this embodiment increased by 86.11%. Compared with the initial magnetic permeability value (1045.92) of the manganese-zinc ferrite material obtained in Comparative Example 2, the initial magnetic permeability value of the manganese-zinc ferrite material prepared in this embodiment increased by 17.83%. Compared with the initial magnetic permeability value (946.19) of the manganese-zinc ferrite material obtained in Comparative Example 3, the initial magnetic permeability value of the manganese-zinc ferrite material prepared in this embodiment increased by 30.25%.

[0091] The frequency characteristic curve and temperature characteristic curve of power loss of manganese-zinc ferrite material obtained by adding VA sintering aid and plasma-assisted ball milling in Example 1 are shown in Figure 7 and Figure 8After testing, the power loss value of the magnetic core in the temperature range of 25℃-120℃ is less than 300kW / m 3 .

[0092] In summary, the present invention prepares a manganese-zinc ferrite powder with low particle size, narrow particle size range and uniformly mixed with VA sintering aid through plasma-assisted ball milling combined with the addition of an appropriate amount of VA sintering aid (V2O5:Al2O3=1:1). The powder can effectively reduce the sintering temperature while improving certain magnetic properties, so that the ferrite pre-sintered material can increase the surface energy of the powder in a relatively short time, and introduce a liquid phase sintering mechanism during the sintering process, thereby reducing the subsequent sintering temperature. In actual production, the steps can be simplified, the cost can be reduced, and the energy consumption can be reduced.

[0093] The above description is only a preferred embodiment of the present application, and does not limit the patent scope of the present application. All equivalent structural changes made by using the contents of the present application specification and drawings under the inventive concept of the present application, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present application.

Claims

1. A method for preparing a low-temperature sintered and low-loss manganese-zinc ferrite material, characterized in that: The following steps are involved: (1) Fe2O3, Mn2O3 and ZnO powders are uniformly mixed and mechanically ball-milled in water; the obtained material is pre-sintered at 850-950°C for 2-4 hours and cooled in the furnace to obtain a ferrite pre-sintered material; (2) adding the following additives to the ferrite pre-sintered material: by mass percentage, CaO: 0.02-0.20%, SiO2: 0.01-0.08%, TiO2: 0.08-0.20%, Co2O3: 0.05-0.18%, V2O5: 0.01-0.40%, Al2O3: 0.01-0.40%, to obtain a mixture, and then performing plasma-assisted ball milling to obtain a refined powder; and then preparing a green sample; (3) The green sample obtained in step (2) is subjected to low-temperature sintering in a nitrogen atmosphere at a sintering temperature of 1050-1250° C. for a sintering time of 2-5 h, and then cooled to obtain a manganese-zinc ferrite material.

2. The preparation method according to claim 1, characterized in that: In step (1), the raw material ratio is, by mole percentage, Fe2O3: 50-55%, ZnO: 10-15%, and Mn2O3: 30-40%.

3. The preparation method according to claim 2, characterized in that: The ball milling medium of the mechanical ball milling in step (1) is stainless steel grinding balls, the ball-to-material ratio is 4±1:1, the ball milling time is 4 to 6 hours, and the material liquid after mechanical ball milling is dried at a temperature of 90 to 120° C. for 6 to 12 hours.

4. The preparation method according to claim 3, characterized in that: The ball milling medium of the plasma-assisted ball milling in step (2) is a tungsten steel alloy grinding ball, the ball-to-material ratio is (40-50):1, the ball milling time is 15-45 minutes, and the vibration frequency is 300-1200 Hz.

5. The preparation method according to claim 4, characterized in that: After the plasma-assisted ball milling is run once, the plasma-assisted ball milling is stopped for 15 to 25 minutes before the next plasma-assisted ball milling is continued. The number of plasma-assisted ball milling is 6 to 10 times.

6. The preparation method according to claim 5, characterized in that: The plasma has a discharge current of 180-250 mA, a discharge voltage of 4.1-4.8 kV, and a discharge frequency of 9-10 kHz.

7. The preparation method according to any one of claims 1 to 6, characterized in that: The temperature rise procedure of the low temperature sintering is: first sinter at 200-400° C. for 1±0.5 h, and then sinter at 1200±50° C. for 3±0.5 h.

8. The preparation method according to claim 7, characterized in that: The temperature rising procedure is: heating to 300±50°C at a rate of 2.5-4.5°C / min, keeping the temperature for 1±0.5h, then heating to 1200°C at a rate of 3-5°C / min, keeping the temperature for 3±0.5h.

9. The preparation method according to claim 8, characterized in that: The step of plasma-assisted ball milling in step (2) is to place the mixed material in a ball mill and wet it with anhydrous ethanol; after evacuating the ball mill, an inert gas is introduced into the ball mill at a pressure of 5×10 -3 ~5×10 -2 MPa, and then ball milling is performed; the nitrogen flow rate in step (3) is 0.01-0.3 L / min.

10. The manganese-zinc ferrite material obtained by the method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • MnZn soft magnetic ferrite material with high frequency, low temperature coefficient and low loss and preparation method thereof

    CN107129291A

  • Powder granularity control method of wideband wide-temperature and low-loss manganese-zinc ferrite

    CN107352992A

  • Atmosphere control method for sintering process of high-frequency wide-temperature low-loss MnZn ferrite

    CN107555984A

  • High-vibration-amplitude magnetoconductivity MnZn ferrite material and preparation method thereof

    CN110054489A

  • Manganese-zinc ferrite pre-sintering material and preparation process thereof

    CN112723872A